The egalitarian conscience essays in honour of G.A. Cohen - Sypnowich, Christine; Cohen, G. A. (Gerald Allan), 1941-2009.; Oxford eBooks (New York ; Oxford : Oxford University Press, 2006)
Bringing together many of the world's leading political philosophers, this volume reflects the wide-ranging themes in the work of G. Cohen. The book contains essays on a number of key topics, united by questions of social justice, pluralism equality, and moral duty.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cohen, G. A. -- 1941-2009.; Equality; Social justice; Communism; Electronic books